(untitled) (Medicine Today, 2017)
We presented a case of 45 years old unmarried woman who complaints of chronic low back pain and diagnosed as a case of Osteitis CondensansIlii (OCI). We are discussing this rare presentation of OCI to increase awareness among the specialty and primary care physicians, as it may be confused with other conditions like- Ankylosing Spondylitis (AS) and inflammatory arthritis. It also prevents misdiagnosis and extensive investigations that not only increase anxiety but are of little benefit. Medicine Today 2016 Vol.28(2): 89-91